Pilot study on selective antimicrobial effect of a halitosis mouthrinse: monospecies and saliva-derived microbiome in an in vitro model system - Márcia Botelho Dinis; Melissa Agnello; Xuesong He; Wenyuan Shi; Nini Chaichanasakul Tran (Journal of Oral Microbiology, 2021)
Background Halitosis refers to malodor emanating from the oral cavity. Several mouthrinses with halitosis-reduction exist on the market, but their effect on the oral microbiome is largely unknown. In this study, we used an efficient in vitro model system to investigate a test mouthrinse's impact on the oral microbiome. Methods Single halitosis-associated species and other common oral microorganism cultures were exposed to the test mouthrinse over time, and their viability was determined by culture-based selective plating. Next, the saliva-derived microbiome from healthy and halitosis-associated individuals was cultured in the presence of the test mouthrinse over time using the previously developed in vitro model system. The microbiome composition was assessed with 16S rRNA gene sequencing and downstream bioinformatics analyses. Results The test mouthrinse displayed antimicrobial activity against known anaerobic bacterial species producing halitosis-related compounds such as Fusobacterium nucleatum, F. periodonticum, and Prevotella intermedia but not against other common oral microorganisms. In the multispecies, saliva-derived cultures, mouthrinse exposure decreased the relative abundance of the Fusobacterium and Prevotella genera while not affecting overall diversity. Conclusions The test mouthrinse had promising anti-halitosis characteristics at the microbiome level, as demonstrated by the reduction in the relative abundance of halitosis-associated taxa while maintaining microbial diversity.